2020
DOI: 10.1038/s41598-020-58923-6
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi Glycoprotein MGAT4D is an Intrinsic Protector of Testicular Germ Cells From Mild Heat Stress

Abstract: Male germ cells are sensitive to heat stress and testes must be maintained outside the body for optimal fertility. However, no germ cell intrinsic mechanism that protects from heat has been reported. Here, we identify the germ cell specific Golgi glycoprotein MGAT4D as a protector of male germ cells from heat stress. Mgat4d is highly expressed in spermatocytes and spermatids. Unexpectedly, when the Mgat4d gene was inactivated globally or conditionally in spermatogonia, or mis-expressed in spermatogonia, sperma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In addition, decreased sperm count, tubular necrosis, and degeneration were observed in the seminiferous tubule lumen, supporting evidence for decreased testicular weight and decreased CASA values compared to the control group. In the HB + HS group, recovery of destroyed seminiferous tubules and normal spermatogenesis were observed in seminiferous tubules, and most recovered from thermal shock except for some seminiferous tubules (Akintayo et al, 2020;Thanh et al, 2020). The results confirmed that HB effectively restores and protects the testicles against thermal shock.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, decreased sperm count, tubular necrosis, and degeneration were observed in the seminiferous tubule lumen, supporting evidence for decreased testicular weight and decreased CASA values compared to the control group. In the HB + HS group, recovery of destroyed seminiferous tubules and normal spermatogenesis were observed in seminiferous tubules, and most recovered from thermal shock except for some seminiferous tubules (Akintayo et al, 2020;Thanh et al, 2020). The results confirmed that HB effectively restores and protects the testicles against thermal shock.…”
Section: Discussionmentioning
confidence: 56%
“…Male germ cells were isolated from the testes of Gm2044-Tg or Non-Tg mice according to our previous study ( Liang et al, 2014 ; Akintayo et al, 2020 ). TRIzol (Invitrogen, Carlsbad, CA) was used to isolate RNA from male germ cells by manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The scrotal heat excitation experiments were performed on mice using the hot water bath method as follws: first, we configured 0.01 mL/g of 5% chloral hydrate (Macklin, Shanghai, China) and turned on the 43°C and 33°C water baths for 1 h. The body weight of mice was measured and male ICR mice of similar body size were categorized into two groups to prepare for the heat stress experiment; mice were anesthetized sequentially according to the measured body weight at an injection volume of 10 µL/g 5% chloral hydrate. The scrotum of anesthetized mice was exposed to a water bath for 25 min at 33°C for the control group, 43°C for the high-temperature group as per the earlier published method (Akintayo et al, 2020), and 43°C for the hyperthermia group. The mice were sacrificed 24 h after testicular heat exposure, and finally, the testes and epididymis were isolated from the mice for histological examination and RNA isolation.…”
Section: Testicular Heat Exposure Model In Micementioning
confidence: 99%